A 87 dB SNR and THD+N 0.03% HiFi grade audio preamplifier - Kok, Chiang-Liang (2024)
This paper presents a significant contribution to high-fidelity audio technology through the comprehensive design and implementation of an advanced audio-grade preamplifier integrated with a high-performance digital-to-analog converter (DAC). The versatility of the digital section allows seamless integration of audio sources from Universal Serial Bus (USB), Bluetooth, or Sony-Philips Digital interface (SPDIF). In addition, the preamplifier accommodates various analog sources, offering flexibility to users. The unique architecture features an innovative resistor network-based DAC and precision components in the analog section, paving the way for achieving unparalleled audio fidelity. The measured distortion values are remarkably low, with a total harmonic distortion plus noise (THD+N) of only 0.03%. Furthermore, the system exhibits a signal-to-noise ratio (SNR) of 87 dB, comparable to industry benchmark. The hardware design sections went into meticulous details, providing an in-depth exploration of each block of the project. The inclusion of test and measurement data from the actual prototype enhances the credibility of the proposed work. This research not only showcases the theoretical operation of the preamplifier and DAC stage but also validates the practical implementation through many rounds of testing and validation. Our proposed work contributes to the field of high-fidelity audio by presenting a novel solution that is comparable to industry standards. The design’s adaptability to many different audio sources, coupled with robust performance metrics, positions it as a benchmark in the field of audio reproduction. The measurement results and findings presented in this paper are poised to influence future advancements in HiFi audio technology.